Interaction of antiepileptic drugs with human P-glycoprotein in vitro - Weiß, Johanna; Kerpen, Christian Johannes; Lindenmaier, Heike; Dormann, Sven-Maria Gregor; Haefeli, Walter E. (The journal of pharmacology and experimental therapeutics, 2003)
About one-third of epilepsy patients are resistant to treatment with antiepileptic drugs (AEDs). This refractoriness is not fully understood, but is thought to be attributed to overexpression of multidrug transporters at the blood-brain barrier, particularly P-glycoprotein (Pgp). In certain cases pharmacoresistance can be overcome by add-on therapy, raising the question of whether the coadministered drugs act as inhibitors of Pgp. Indeed, several AEDs are substrates and to some extent also inducers of Pgp. To date nothing is known about possible Pgp inhibitory activities of AEDs. Therefore, we investigated whether AEDs commonly used in mono or add-on therapy inhibit Pgp using a calcein acetoxymethylester uptake assay with L-MDR1 cells and primary porcine brain capillary endothelial cells, as well as confocal laser-scanning microscopy with L-MDR1 cells and bodipy-verapamil as Pgp substrate. In the calcein assay only carbamazepine inhibited Pgp, which was confirmed in confocal laser-scanning microscopy. In this assay, also phenytoin, lamotrigine, and valproate revealed Pgp inhibitory potency. Because Pgp inhibition by AEDs appeared at significantly higher concentrations than that of well known inhibitors and because the effective concentrations exceeded therapeutic AED plasma concentrations, Pgp inhibition appears not to be of clinical relevance, at least in antiepileptic monotherapy. However, it is possible that this inhibition may contribute to the effectiveness of certain add-on therapies.